Time-dependent rheological behavior of natural polysaccharide xanthan gum solutions in interrupted shear and step-incremental/reductional shear flow fields - Lee, Ji-Seok; Song, Ki-Won (Korea-Australia rheology journal, 2015)
The objective of the present study is to systematically elucidate the time-dependent rheological behavior of concentrated xanthan gum systems in complicated step-shear flow fields. Using a strain-controlled rheometer (ARES), step-shear flow behaviors of a concentrated xanthan gum model solution have been experimentally investigated in interrupted shear flow fields with a various combination of different shear rates, shearing times and rest times, and step-incremental and step-reductional shear flow fields with various shearing times. The main findings obtained from this study are summarized as follows. (i) In interrupted shear flow fields, the shear stress is sharply increased until reaching the maximum stress at an initial stage of shearing times, and then a stress decay towards a steady state is observed as the shearing time is increased in both start-up shear flow fields. The shear stress is suddenly decreased immediately after the imposed shear rate is stopped, and then slowly decayed during the period of a rest time. (ii) As an increase in rest time, the difference in the maximum stress values between the two start-up shear flow fields is decreased whereas the shearing time exerts a slight influence on this behavior. (iii) In step-incremental shear flow fields, after passing through the maximum stress, structural destruction causes a stress decay behavior towards a steady state as an increase in shearing time in each step shear flow region. The time needed to reach the maximum stress value is shortened as an increase in step-increased shear rate. (iv) In step-reductional shear flow fields, after passing through the minimum stress, structural recovery induces a stress growth behavior towards an equilibrium state as an increase in shearing time in each step shear flow region. The time needed to reach the minimum stress value is lengthened as a decrease in step-decreased shear rate.